Volumetric-Modulated Arc Therapy: Effective and Efficient End-to-End Patient-Specific Quality Assurance - O’Daniel, Jennifer; Das, Shiva; Wu, Q. Jackie; Yin, Fang-Fang (International journal of radiation oncology, biology, physics, 2012)
To explore an effective and efficient end-to-end patient-specific quality-assurance (QA) protocol for volumetric modulated arc radiotherapy (VMAT) and to evaluate the suitability of a stationary radiotherapy QA device (two-dimensional [2D] ion chamber array) for VMAT QA. Three methods were used to analyze 39 VMAT treatment plans for brain, spine, and prostate: ion chamber (one-dimensional absolute, n = 39), film (2D relative, coronal/sagittal, n = 8), and 2D ion chamber array (ICA, 2D absolute, coronal/sagittal, n = 39) measurements. All measurements were compared with the treatment planning system dose calculation either via gamma analysis (3%, 3- to 4-mm distance-to-agreement criteria) or absolute point dose comparison. The film and ion chamber results were similarly compared with the ICA measurements. Absolute point dose measurements agreed well with treatment planning system computed doses (ion chamber: median deviation, 1.2%, range, −0.6% to 3.3%; ICA: median deviation, 0.6%, range, −1.8% to 2.9%). The relative 2D dose measurements also showed good agreement with computed doses (>93% of pixels in all films passing gamma, >90% of pixels in all ICA measurements passing gamma). The ICA relative dose results were highly similar to those of film (>90% of pixels passing gamma). The coronal and sagittal ICA measurements were statistically indistinguishable by the paired t test with a hypothesized mean difference of 0.1%. The ion chamber and ICA absolute dose measurements showed a similar trend but had disparities of 2-3% in 18% of plans. After validating the new VMAT implementation with ion chamber, film, and ICA, we were able to maintain an effective yet efficient patient-specific VMAT QA protocol by reducing from five (ion chamber, film, and ICA) to two measurements (ion chamber and single ICA) per plan. The ICA (Matrixx®, IBA Dosimetry) was validated for VMAT QA, but ion chamber measurements are recommended for absolute dose comparison until future developments correct the ICA angular dependence.